Changes in Serum CRP and PCT Levels in Patients with Acute Simple Lower Urinary Tract Infection and Evaluation of the Efficacy of Treatment with Shuangdong Capsules - Yachun Tang; Qun Zhou (Emergency Medicine International)
Objective. The aim of this study is to investigate the changes and significance of serum C-reactive protein (CRP) and procalcitonin (PCT) levels in patients with acute simple lower urinary tract infection (ALUTI) and to analyze the efficacy of treatment with Shuangdong capsules, so as to provide a basis for the rational clinical application of drugs. Methods. 92 patients with ALUTI (observation group) were randomly divided into 46 cases each in group A and group B. Group A was treated with basic anti-infective drugs, while group B was treated with Shuangdong capsules, and the duration of treatment in both groups was 14 days. The curative effect of the two groups was analyzed, and the changes in serum PCT and CRP levels were compared before and after treatment and compared with 40 healthy people in the control group. Results. The serum PCT and CRP levels, the number of urinary leukocyte count (LEU), and the number of urinary bacterial count (BACT) were significantly higher in Group A and Group B than in the healthy control group before treatment (P<0.05). After treatment, the total clinical efficiency of patients in group B (97.83%) was significantly higher than that in group A (78.26%) (P<0.05). The serum PCT and CRP levels, the number of urinary LEU, and the number of urinary BACT decreased in both groups after treatment compared with those before treatment, and all of them were significantly lower in group B than in group A (P<0.05). The area under the curve (AUC) values of serum PCT and CRP levels for the diagnosis of acute simple lower urinary tract infection were 0.747 (95% CI 0.633–0.860) and 0.926 (95% CI 0.870∼0.982), both with high sensitivity and specificity. Conclusion. The Shuangdong capsule combined with conventional antibacterial drugs has better clinical efficacy in the treatment of acute simple lower urinary tract infection; serum CRP and PCT levels in patients with acute simple lower urinary tract infection can be used as indicators for diagnosis and efficacy determination of the infection.